Microscale Adaptation of In Vitro Transcription/Translation for High‐Throughput Screening of Natural Product Extract Libraries. (25th July 2015) - Lowell, Andrew N.; Santoro, Nicholas; Swaney, Steven M.; McQuade, Thomas J.; Schultz, Pamela J.; Larsen, Martha J.; Sherman, David H.
Abstract : Novel antimicrobials that effectively inhibit bacterial growth are essential to fight the growing threat of antibiotic resistance. A promising target is the bacterial ribosome, a 2.5 MDa organelle susceptible to several biorthogonal modes of action used by different classes of antibiotics. To promote the discovery of unique inhibitors, we have miniaturized a coupled transcription/translation assay using E. coli and applied it to screen a natural product library of 30 000 extracts. We significantly reduced the scale of the assay to 2 μ L in a 1536‐well plate format and decreased the effective concentration of costly reagents. The improved assay returned 1327 hits (4.6% hit rate) with %CV and Z′ values of 8.5% and 0.74, respectively. This assay represents a significant advance in molecular screening, both in miniaturization and its application to a natural product extract library, and we intend to apply it to a broad array of pathogenic microbes in the search for novel anti‐infective agents. Abstract : A coupled transcription/translation high‐throughput screening assay was miniaturized and shown to be effective at detecting known classes of ribosome‐inhibiting antibiotics. This luciferase‐based assay was successfully applied to a natural product extract library of 30 000 compounds with a hit‐rate of 4.6%, a %CV value of 8.5% and a Z ' value of 0.74. Selected hits were retested in triplicate to confirm authenticity, subjected to a secondary screen to remove luciferase inhibitors, and are moving forward in the discovery process..